Coronary artery spasm following on-pump coronary artery bypass grafting with 20 months follow-up - Kowalówka, Adam R.; Malinowski, Marcin; Onyszczuk, Magdalena; Deja, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
We report on a 69-year-old woman who demonstrated native coronary artery and grafted vessel spasm following on-pump coronary artery bypass grafting (CABG). Despite intraaortic balloon pump (IABP) insertion, electrocardiogram (ECG) abnormalities did not disappear. Emergency coronary angiography (CAG) was performed. The patient was successfully treated with systemic and intracoronary injection of vasodilator agents. ECG changes disappeared, with normalized and stable hemodynamic function. Intraaortic balloon pump was maintained for 48 h. The patient was discharged in good clinical condition. Coronary artery spasm (CAS) may result in life-threatening arrhythmias, circulatory collapse or death. The etiology of CAS is multifactorial and includes heart manipulation, exogenous vasoconstrictors, stress-related catecholamine release, hypoxia and oxidative stress. Postoperative CAS is most commonly manifested by ST-segment elevation and circulatory collapse without specific causes. The gold standard for revealing CAS is CAG. Infusion of vasodilators combined with IABP is adequate in most instances, but extracorporeal membrane oxygenation has been necessary for more extensive or resistant coronary spasm.